Evaluating the paleoclimatic significance of clay mineral records from a late Pleistocene loess-paleosol section of the Ili Basin, Central Asia. Issue 3 (18th October 2017) - Li, Yue; Song, Yougui; Zeng, Mengxiu; Lin, Weiwei; Orozbaev, Rustam; Cheng, Liangqing; Chen, Xinli; Halmurat, Tiliwaldi
Abstract: In this study, we present clay mineral records from a late Pleistocene loess-paleosol sequence in the Ili Basin, Central Asia, and assess their significance for paleoclimatic reconstruction. The results show that the clay minerals are mainly illite (average 60%) and chlorite (28%), with minor kaolinite (9%) and smectite (3%). Illite was of detrital origin with no obvious modification to its crystal structure. Increases in illite content in the loess are ascribed to wind intensity rather than pedogenesis. High proportions of illite in the clay fraction, and of muscovite in the bulk samples of the paleosol units, may lead to an overestimation of the weathering intensity. Kaolinite was likely inherited from the sedimentary rocks, while chlorite might have been inherited from both sedimentary and metamorphic rocks. The paleoclimatic signals of kaolinite and chlorite were unclear, due to reworking by both fluvial and eolian systems. Smectite was more likely formed by the transformation of biotite and illite, and its variation in the loess sequence was also controlled by wind intensity; this was largely due to aggregation and is unlikely to reflect moisture changes. Although the interpretation of paleoclimate evolution may contain some uncertainties, clay mineralogy does provide the possibility of tracing dust provenance.